Conflictos interparentales vistos desde los estudiantes del grado sexto de una Institución Educativa de Riohacha. (2021)
The following study aims to analyze the parental conflicts present between the students of the 603rd year of the Isabel María Cuesta educational institution of the special area tourism and culture of Riohacha, and through research This study aims to give responses and Ensure that future conflicts that arise between the parents and anyone who is its origin, remain less complicated to solve, in order to achieve its objectives